A MONOGRAPH OF CARYODAPHNOPSIS A. SHAW - a. j. g. h. kostermans (REINWARDTIA, 1974)
Of the genus Caryodapknopaia 7 species are known, of which two are described here for the first time.The genus occurs from Yunnan to Indochina,with the exception of C.tonkinensis,which goes as far as the Philippines and Borneo. Apparently most species are distributed by water and C.tonkinensis is assumed to have spread from the mainland to Borneo during the glacial period,when a land connection existed.The genus is related to Nothaphoebe and Alseodaphne and hence belongs to Perseae.